Parenting Style in Developing the Character of Elementary School Student Responsibility - Ipung Purwati; Markhamah Markhamah; Anatri Desstya; Minsih Minsih (STAI Hubbulwathan Duri, 2023)
Character education in learning plays a role in helping students to grow good character that can be realized in their social life. Character education can also play a role so that students want to independently learn the material and develop an attitude of responsibility towards the tasks given by the teacher. This study aims to analyze the parenting style of parents in developing the responsibility of children ata private elementary school. The research employed a qualitative descriptive methodology. This study methodology employs many data collection techniques, including observation, interviews, documentation, and questionnaires. This investigation employed the Miles and Huberman model as the data analysis technique. The outcome of his research pertains to the influence of parenting on the development of kid responsibility. Parenting greatly affects children's development and growth. Effective and suitable parenting practises help children grow and develop, whereas insufficient parenting might hinder their growth. Student accountability is directly related to parental attitudes. Parents must consider their children's particular qualities and developmental needs, including their age, while using effective parenting practises. Parents must also be patient, open, and eager to listen to their children when faced with obstacles or needs. Parents may help their children grow and develop into well-rounded, moral people by using successful and suitable parenting practises.